2015
DOI: 10.1103/physrevlett.115.257403
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Dark Excitons in MonolayerWSe2

Abstract: Transition metal dichalcogenides in the class MX_{2} (M=Mo, W; X=S, Se) have been identified as direct-gap semiconductors in the monolayer limit. Here, we examine light emission of monolayer WSe_{2} using temperature-dependent photoluminescence and time-resolved photoluminescence spectroscopy. We present experimental evidence for the existence of an optically forbidden dark state of the band-gap exciton that lies tens of meV below the optically bright state. The presence of the dark state is manifest in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
302
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 434 publications
(333 citation statements)
references
References 63 publications
28
302
3
Order By: Relevance
“…In addition, relaxation of the exciton population toward intervalley K−K′ 47 and K-Q/Σ states 30 is possible. However, due to the similar binding energies of the different states and the broadening of the measured 1s−2p resonance, the excitons in our experiment should be generally considered as a mixture of these configurations.…”
Section: Nano Lettersmentioning
confidence: 99%
“…In addition, relaxation of the exciton population toward intervalley K−K′ 47 and K-Q/Σ states 30 is possible. However, due to the similar binding energies of the different states and the broadening of the measured 1s−2p resonance, the excitons in our experiment should be generally considered as a mixture of these configurations.…”
Section: Nano Lettersmentioning
confidence: 99%
“…In addition, WSe 2 possesses good luminescence at room temperature (RT) and reasonable emission at low temperatures (LT). Finally, prior studies have confirmed the existence of excitons, trions [34,38,48] and more recently even biexcitons [49] and dark excitons [50]. Ultimately, the role of the dielectric environment and surface properties on excitons shall be unravelled in detail soon.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding transitions are denoted as K À K 0 and K À L in the following. In a recent time-resolved and temperaturedependent photoluminescence study, the existence of such dark intervalley excitons was experimentally demonstrated 14 . In particular, it was shown that in tungsten-based TMDs, the intervalley dark excitonic state lies energetically below the optically accessible exciton, resulting in a strong quenching of photoluminescence at low temperatures 14,15 .…”
mentioning
confidence: 99%